Characterization and detection of and phylogenetic relationships among Xanthomonas oryzae pv. oryzae isolates from selected rice varieties in Peninsular Malaysia - Keshavarzi, Kavous (2012)
Rice (Oryza sativa) is one of the most important food crops in the world and the major crop of Malaysia after oil palm. Bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv oryzae (Xoo) is the most important disease in Malaysia. Paddy leaves or stems showing symptoms of disease were collected from rice fields in Penang, Kedah, Selangor, and Melaka in Peninsular Malaysia during the period from 2008 to 2010. The isolated bacteria were found to be oxidase negative, gram negative, anaerobic growth negative and did not produce fluorescent pigment. Thirty collected strains showed leaf blight symptoms on inoculated rice plants, hypersensitive reaction on tobacco, and hydrolysis on gelatin. Pathogenic tests on two rice varieties MR84 and IR8 showed that significant differences were observed between 30 strains. All strains of Xoo were classified into four groups, i.e. non virulent, slightly virulent, moderately virulent and highly virulent. Seven strains, including MXO1 and SX08 were highly virulent, five strains (including SXO1 and MX06) were moderately virulent, while 17 strains represented by PX043 and KXO182 showed low virulence, and the only non-virulent strain was PX036. It can be concluded that there is a relation between location and severity of disease that the most and the lowest severity was related to the strains of Melaka and Penang respectively and also the strains from the different rice-growing areas or states were diverse and differed in their degree of virulence. For detection of Xoo, infected tissues were crushed and the DNA was extracted using a modified CTAB method. A PCR product of about 470 bp was produced using the XOR-FIXOR-R2 primer pair that amplified the 16S-23S intergenic rDNA sequence region. Comparison indicated that the 30 strains have 98% to 99% nucleotide homology to the sequences of 16S- 23S rDNA of Xoo accessions AB026287 and AY251004 from Japan and China, respectively. Another PCR product of about 964 bp was generated by the primer pair TXT/TXT4R that amplified the insertion sequence element IS1113 and had 99% homology to the sequences of the Xoo accessions GU982970 and AF482989 from India and USA, respectively. According to these results, the causal agent of bacterial leaf blight of rice could be identified in less than three hours. Phylogeny analysis among Malaysian strains indicated genomic diversity of Xoo strains exist throughout Malaysia. Additionally, strains of Xoo could be divided into two main groups, namely Penang- Kedah and Selangor-Melaka that are neighboring states respectively an indication that geographical area is the predominant factor influencing strain variability. And also in the states the diversities of Xoo collected from rice cultivars generally were similar. The generated banding patterns resulting from the amplification of DNA templates of the 30 Xoo strains by REP, ERIC and BOX pnmers were reproducible as was proven with at least three PCR replications, suggesting the suitability of using these primers as markers for genetic studies of Xoo. There was a slight difference between the phylogenetic tree patterns derived from respective REP, ERIC and BOX primer sets. The primers generated four common amplification bands in all strains tested, of the sizes 200, 400, 500 and 800 bp. Cluster analysis based on REP, ERIC and BOX primer sets and the pooled data resulting from all three primers (BER primer) indicated that the 30 Xoo strains were divided into two main groups with similarity between about 60% or into four subgroups, representing strain from Penang, Kedah, Selangor and Melaka. Based on these results, there were significant similarities among 30 strains of Xoo that have been collected from the same origin in Malaysia, indicating that Xoo strains originating from different geographic regions in Peninsular Malaysia were phylogenetic ally different. Hence, this research indicated that strains of Xoo isolated from Malaysia are pathologically, genetically and geographically diverse.